Knowledge, attitudes, and practices regarding fertility preservation among women of childbearing age in southern China: a cross-sectional study - Zhang, Yan; An, Juan; Hua, Fanglan; Wei, Yanhong; Shu, Fanglian (Frontiers in Public Health, 2025)
ObjectiveThis study aimed to investigate the knowledge, attitudes and practices regarding fertility preservation among women of childbearing age and to analyse the factors influencing these behaviours.MethodsA cross-sectional survey of 294 women of childbearing age (18–49 years) was conducted in urban healthcare settings between January 2024 and March 2024 using convenience sampling; it assessed fertility preservation behaviours and health beliefs through a structured questionnaire and multiple regression analysis.ResultsAmong the participants, 62.93% reported prior awareness of fertility-related concepts. Healthcare workers constituted the largest occupational group (45.24%), and 80.61% had a college education or above. High compliance was observed in personal hygiene (85.03%) and avoidance of smoking (71.77%), whereas only 31.97% regularly underwent fertility assessments. Health belief analysis revealed high levels of perceived susceptibility (87.41%) and perceived benefits (89.79%). Multiple regression analysis identified education level (β = 0.326, p < 0.001), healthcare occupation (β = 0.284, p < 0.001) and perceived benefits (β = 0.253, p < 0.001) as significant predictors of fertility preservation behaviours. Main barriers included time constraints (50.34%) and financial concerns (25.17%).ConclusionDespite high awareness of the importance of fertility preservation, significant gaps exist between knowledge and practice. Education level, healthcare occupation and perceived benefits strongly influence protective behaviours. These findings suggest the interventions should not only enhance health education but also address structural obstacles, such as cost and accessibility, to bridge the gap between knowledge and action.